The Influence Of The Role Of Public Relations In Improving The Image Of Institutions In BPSDM West Java - Insani, Siti; Rahman, Deri (JAKI : Jurnal Akuntansi, 2025)
In the era of rapid digital transformation, public institutions are increasingly required to maintain a positive and credible image to gain public trust. Public relations (PR) plays a strategic role in this process by facilitating effective communication, fostering transparency, and enhancing institutional reputation. This study investigates the influence of public relations on institutional image, with a focus on the West Java Province Human Resources Development Agency (BPSDM). Utilizing a quantitative research method with a causal associative approach, data were collected through structured questionnaires distributed both online and offline to individuals who had interacted with BPSDM. The findings indicate a strong and statistically significant relationship between the role of public relations and the formation of a positive institutional image. The coefficient of determination (R²) reached 0.820, suggesting that 82% of the changes in public perception are influenced by PR efforts. BPSDM’s use of digital platforms, especially Instagram, has proven effective in disseminating information, engaging with the public, and strengthening institutional visibility. Various content strategies—ranging from informative to interactive are employed to reach diverse audiences. Regular evaluation of engagement metrics such as likes, comments, and views supports continuous improvement in communication strategies. This study highlights the importance of positioning public relations as a core element in institutional management, not merely as a supportive function. Government institutions, therefore, are encouraged to invest in digital communication capabilities and strategic public relations planning to foster sustainable public trust and a resilient institutional image.